KOMUNIKASI POLITIK DAN KONFLIK DALAM KEBIJAKAN PEMERINTAH (Studi Kasus Konflik Kebijakan Antara Legislatif Dan Eksekutif Di Kabupaten Buton Selatan, Sulawesi Tenggara) - Ansar Suherman (SOURCE : Jurnal Ilmu Komunikasi, 2016)
Executive policy-related polemics often leads to war of opinion that led to a conflict with the legislature, one of which is the formulation of the Draft Regulation (Ranperda) on Spatial Planning (Spatial) Buton Selatan Regency. This study aims to determine the pattern of the relationship between the executive and legislative communications along with constraints and problems encountered in the implementation of the authority and form of the conflict between the executive and the legislature in lawmaking Spatial Buton Selatan. The method used is qualitative approach. Data obtained directly by using interviews with informants about the conflict in political communication in addressing regional legislative policy as the executive regent Buton Selatan on Spatial Ranperda Buton Selatan. The data in thisstudy using the model data analysis komponensial (componential anaylisis). The results showed that the pattern of the relationship between the executive and legislative communication in conflict resolution in the determination of Buton Selatan Spatial regulation is through the process of formal organizational communication and informal organizational communication. Form of the conflict between the executive and the legislature in lawmaking Spatial Buton Selatan Regency is a conflict between organizations, between the executive and legislative of Buton Selatan Regency. Keywords: Political Communication, Conflict, Policy, Executive, Legislative.